Unlocking the application potential of electrocoagulation process through hybrid processes. (April 2021) - Almukdad, Abdulkarim; Hafiz, MhdAmmar; Yasir, Ahmed T.; Alfahel, Radwan; Hawari, Alaa H.
Highlights: EC coupled with other process reduces barriers of individual processes. Long-term evaluation is needed to evaluate energy efficiency of hybrid EC processes. More pilot scale studies are required for EC based hybrid process. Utilizing dielectrophilic enhanced electrodes may reduce the electrode consumption. Numerical models must be developed to predict the performance of EC hybrid process. Abstract: Electrocoagulation (EC) has attracted attention during the recent years due to its ease of use and high removal rate of organic and inorganic pollutants. It was found that using EC as a pretreatment process can decrease the overall energy consumption and improve the treated water quality. This literature review evaluates the efficiency of integrating EC process with other water treatment processes including membranes, chemical, electromagnetic and oxidation processes. The studied technologies were ultrafiltration (EC-UF), reverse osmosis (EC-RO), forward osmosis (EC-FO), membrane distillation (EC-MD), forward osmosis-membrane distillation (EC-FO-MD), membrane bioreactor (EC-MBR), electrodialysis (EC-ED), ozonation (EC-O3 ), ultraviolet (EC-UVC/VUV), peroxi-electrocoagulation (EC-H2 O2 ), activated carbon adsorption (EC-AC), biofiltration (EC-BF) and electro-oxidation (EC-EO). The overall performance was evaluated using pollutants removal efficiency, energy consumption and operational cost. Then, the performance of pilot scale hybrid electrocoagulation processes and the current status of implementation was discussed. The future potential of electrocoagulation lies with proper hybridization of EC with other water treatment processes that would minimize the overall cost and enhance quality of the treated water.